Multi period performance assessment model for the site property management - Lin, Yung-Yu; Pan, Nai-Hsin (International Journal of Strategic Property Management, 2014)
Performance assessment is an important task for the property management company to measure the performance of site, to evaluate and rank the sites, and to trace the main indices resulting in worse performance. Therefore, this study proposes a multi period performance assessment model. A performance scale with twelve indices is adopted to measure the site performance. The raw data can be transformed to be comparable by the proposed linear preprocessing method with specification limits. The priority is ranked by the integrated method with the technique for order preference by similarity to ideal solution and the signal-to-noise ratio. Finally, the main indices resulting in worse performance can be identified by the proposed tracing method. An illustrative example of real case is adopted to demonstrate the feasibility and practicability of the proposed model. Results show the proposed model can obtain a more reliable result. First Publish Online: 8 Dec 2014